Mathematics Students’ Retention Using Algebrator Software in Port Harcourt Metropolis, Nigeria - Onyekachi Uchechukwu Ahumaraeze; Ekene Esther Ndubisi (Pendidikan Matematika STKIP Kusuma Negara, 2025)
The study focused on improving students’ retention in mathematics using Algebrator Softwares in Port Harcourt Metropolis, Nigeria. It examined the effect of Algebrator-based instruction, gender influence, and the interaction between instructional strategy and gender on retention in Algebra. A quasi-experimental research design was employed. Using a quasi-experimental design, 154 senior secondary students (94 experimental, 60 control) were selected through purposive sampling from a population of 21,079. The experimental group was taught using Algebrator software, while the control group received traditional lecture-based instruction. Data were collected via a validated Mathematics Retention Test on Algebra (MRTA) and analyzed using mean, standard deviation, and analysis of covariance. The findings of the study showed that students taught with Algebrator software showed significantly higher retention in Algebra than those taught through lectures. Gender had no significant effect on retention, and no interaction was found between instructional strategy and gender. It was recommended, among other suggestions, that Algebrator Software should be used to teach Mathematics especially Algebra to advance students' retention.